2011
DOI: 10.1088/0004-637x/728/1/52
|View full text |Cite
|
Sign up to set email alerts
|

INTERGALACTIC TRANSMISSION AND ITS IMPACT ON THE Lyα LINE

Abstract: We study the intergalactic transmission of radiation in the vicinity of the Lyα wavelength. Simulating sightlines through the intergalactic medium (IGM) in detailed cosmological hydrosimulations, the impact of the IGM on the shape of the line profile from Lyα emitting galaxies at redshifts 2.5 to 6.5 is investigated. In particular we show that taking into account the correlation of the density and velocity fields of the IGM with the galaxies, the blue part of the spectrum may be appreciably reduced, even at re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
335
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(360 citation statements)
references
References 80 publications
20
335
0
Order By: Relevance
“…This might be the reason for the high τ d preference of the data. However, for the observed spectra the blue side might be attenuated not by dust but by neutral gas in the CGM and / or IGM which scatters Lyα photons out of the line-of-sight, and thus, effectively absorb the blue side of the spectrum (Dijkstra et al 2007;Laursen et al 2011). …”
Section: Fitting Resultsmentioning
confidence: 99%
“…This might be the reason for the high τ d preference of the data. However, for the observed spectra the blue side might be attenuated not by dust but by neutral gas in the CGM and / or IGM which scatters Lyα photons out of the line-of-sight, and thus, effectively absorb the blue side of the spectrum (Dijkstra et al 2007;Laursen et al 2011). …”
Section: Fitting Resultsmentioning
confidence: 99%
“…The "true" IGM only affects the strength of Lyα red peak by the damped absorption factor of e −τ , where τ is the optical depth of the IGM HI gas along the line of sight, and its effect on the velocity of the narrow Lyα red peak is negligible. Some simulations suggested that the HI gas in the CGM can be very close to the Lyα photons in frequency, so the CGM HI gas can resonantly scatter and/or absorb Lyα photons at V(redpeak)<160 km s −1 (Laursen et al 2011;Dijkstra 2014) and change the V(red-peak) of Lyα profile. In fact those scatterings by CGM are part of the Lyα escape process before Lyα photons reach the "true" IGM.…”
Section: Predicting Lyα Escape Fractionmentioning
confidence: 99%
“…As a result, the inflow feature in our profiles may disappear and the shape may become an asymmetric single peak with only photons at the red wing. Laursen et al (2011) showed that a large fraction of Lyα flux from galaxies atz 6.5 could be lost by scattering in IGM despite most of the IGM being ionized. As a simple test, we show the line profiles without photons at shorter wavelength as (Laursen et al 2011). shown in the blue dashed lines in the figure.…”
Section: The Lyα Line Profilementioning
confidence: 99%